Analisis Pengaruh Kualitas Pelayanan Terhadap Tingkat Kepuasan Taruna di Politeknik Penerbangan Surabaya - Bambang Wasito; Sri Lestari (Jurnal Penelitian)
In this research of writer use method either through qualitative and also quantitatively with examination of reliabilitas and validity, test doubled regresi, correlation coefficient test, parsial correlation coefficient test, test F test and t. As for result of this research is : For the examination of by parsial known by variable (tangibles) (X1), assess t calculate which obtained is equal to 9,547 and its value is 0,000, (reliability) (X2), assess t calculate which obtained is equal to 10,245 and its value is 0,000, (responsiveness) (X3), assess t calculate which obtained is equal to 8,576 and its value is 0,001, (assurance) (X4), assess t calculate which obtained is equal to 7,568 and its value is 0,002, (empathy) (X5), assess t calculate which obtained is equal to 6,125 and its value is 0,000, this smaller value than = 0,05, so that can be said that that free variable (tangibles) (X1), (reliability) (X2), (responsiveness) (X3), (assurance) (X4), (empathy) (X5) by parsial have an effect on to storey; level satisfaction of cadets (Y) at Aviation Polytechnic of Surabaya. Result of calculation Test conducted F constructively SPSS program obtained [by] f value [count/calculate] equal to 980,365. obtained Signifikansi value [is] equal to 0,000, this smaller signifikansi value than value that is 0,05. Thereby can be interpreted that free variable which (tangibles) (X1), (reliability) (X2), (responsiveness) (X3), (assurance) (X4), (empathy) (X5), together have an effect on to storey; level satisfaction of cadets (Y) at Aviation Polytechnic of Surabaya. Because X2 variable that is (reliability) have highest parsial correlation value that is equal to 0,988 compared to other free variable hence X2 variable that is (reliability) represent dominant free variable influence variable tied that is storey; level satisfaction of cadets (Y) at Aviation Polytechnic of Surabaya.